Effects of off- and pre-season training on aerobic and anaerobic power of kayak paddlers - Isaka, T.; Takahashi, K. (Medicine & Science in Sports & Exercise, 1997)
The effects of off- and pre-season training of racing canoeists on aerobic and anaerobic power output were evaluated. Varsity kayakers (N = 12) were studied. The following were found: Anaerobic alactic power and anaerobic lactic power did not change during the off-season but increased significantly during pre-season training. VO2max increased significantly during off-season training probably because aerobic long-distance running and paddling were the principal activities. Aerobic training did not affect anaerobic variables. Implication: Training responses largely reflect the type of training that is experienced. When practice, such as pre-season training, involves only aerobic work, the anaerobic energy system is not stimulated because of specific (restricted) training effects.